Onion (Allium cepa L.) peel: A review on the extraction of bioactive compounds, its antioxidant potential, and its application as a functional food ingredient. Issue 10 (13th September 2022) - Kumar, Manoj; Barbhai, Mrunal D; Hasan, Muzaffar; Dhumal, Sangram; Singh, Surinder; Pandiselvam, Ravi; Rais, Nadeem; Natta, Suman; Senapathy, Marisennayya; Sinha, Neha; Amarowicz, Ryszard
Abstract: Functional food development is rapidly increasing as a result of consumer consciousness concerning healthy and nutritious foods. In turn, research exploring novel ingredients for formulating functional foods has been accelerated. Onion peel or skin is a byproduct obtained from onion processing that contains abundant phytochemicals, contributing to its antioxidant potential. The main focus of this review is to highlight different extraction techniques (both conventional and nonconventional) that can be implemented to extract the bioactive compounds from onion peel and assess their antioxidant activity. Furthermore, this review highlights the major areas for the application of onion peel and its extract as prospective functional ingredients, thus aiding in the preparation of designer foods with additional health benefits. The use of onion peel could also assist in redesigning popularly consumed processed foods, such as baked products, noodles or pasta, as packaging material, meat quality improvers, colorants, and juice clarifiers. This review serves as a preliminary document that can assist in exploring different ways of incorporating bioactive onion peels or skin into the functional food industry and concludes that future research can assist in the effective and efficient utilization of this resource.